2021
DOI: 10.3389/fmats.2021.735344
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electronic Properties of CVD Monolayer Hexagonal Boron Nitride by an Atomic Force Microscope

Abstract: Ultrathin hexagonal boron nitride (h-BN) has recently attracted a lot of attention due to its excellent properties. With the rapid development of chemical vapor deposition (CVD) technology to synthesize wafer-scale single-crystal h-BN, the properties of h-BN have been widely investigated with a variety of material characterization techniques. However, the electronic properties of monolayer h-BN have rarely been quantitatively determined due to its atomically thin thickness and high sensitivity to the surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The pre-existing background carrier concentration n e0 in our sample can be estimated as follows. Using a similar growth technique as ours, Chen et al reported a resistivity of 529 Ωcm for monolayer hBN flakes [43]. Assuming an electron mobility of 35 cm 2 (V • s) −1 [44], this translates to a background carrier density of n e0 ∼ 10 8 cm −3 .…”
Section: Role Of Defects In Optical Breakdownmentioning
confidence: 50%
“…The pre-existing background carrier concentration n e0 in our sample can be estimated as follows. Using a similar growth technique as ours, Chen et al reported a resistivity of 529 Ωcm for monolayer hBN flakes [43]. Assuming an electron mobility of 35 cm 2 (V • s) −1 [44], this translates to a background carrier density of n e0 ∼ 10 8 cm −3 .…”
Section: Role Of Defects In Optical Breakdownmentioning
confidence: 50%